Amycolatopsis kentuckyensis sp. nov., Amycolatopsis lexingtonensis sp. nov. and Amycolatopsis pretoriensis sp. nov., isolated from equine placentas - Labeda, D P; Donahue, J M; Williams, N M; Sells, S F; Henton, M M (International journal of systematic and evolutionary microbiology, 2003)
Actinomycete strains isolated from lesions on equine placentas from two horses in Kentucky and one in South Africa were subjected to a polyphasic taxonomic study. Chemotaxonomic and morphological characteristics indicated that the isolates are members of the genus AMYCOLATOPSIS: On the basis of phylogenetic analysis of 16S rDNA sequences, the isolates are related most closely to Amycolatopsis mediterranei. Physiological characteristics of these strains indicated that they do not belong to A. mediterranei and DNA relatedness determinations confirmed that these strains represent three novel species of the genus Amycolatopsis, for which the names Amycolatopsis kentuckyensis (type strain, NRRL B-24129(T)=LDDC 9447-99(T)=DSM 44652(T)), Amycolatopsis lexingtonensis (type strain, NRRL B-24131(T)=LDDC 12275-99(T)=DSM 44653(T)) and Amycolatopsis pretoriensis (type strain, NRRL B-24133(T)=ARC OV1 0181(T)=DSM 44654(T)) are proposed.